Regionalized acceptance analysis of an agricultural energy management system in Germany - Bader, Christoph; Groß, Eberhard; Stumpenhausen, Jörn; Egger, Theresa; Hartl, Laura; Bernhardt, Heinz (Frontiers in Energy Research, 2025)
In view of rising demand, energy is becoming a significant production and cost factor in industry and the economy. In addition to the consequences of climate change, the energy markets are tense and volatile due to inflation, war and higher borrowing costs. As a result of society’s desire to phase out the use of fossil fuels, the focus is shifting to renewable energies as an alternative worldwide, but especially in Germany. In addition to industry, rural areas and agriculture, especially energy-intensive livestock farms, are also affected by this development and face additional economic challenges. Additional energy can be generated through the use of photovoltaic systems on the roofs of agricultural buildings or the operation of biogas plants. However, in order to be able to use the potential for renewable energy generation efficiently at all, intelligent electricity storage concepts and a globally unique energy management system (EMS) are absolutely essential in order to coordinate both inter-farm production processes and the varying energy demand in the electricity grid with the supply. As farms differ greatly both in terms of equipment and in terms of region, the question of a comprehensive market launch arises. The success or failure of this will depend to a large extent on user acceptance and application. The aim of this study is to use the web-based software tool ADOPT to forecast and predict the level of acceptance and the duration of the future market launch of the EMS innovation. Different regions in Germany (Bavaria, North Rhine-Westphalia, Mecklenburg-Western Pomerania) were selected in order to compare possible operational and region-specific differences. A very positive forecast result of 97%–98% after a market introduction period of around 8 years shows an optimistic trend. However, the ADOPT tool analyzes various influencing factors in parallel in a sensitivity analysis, which serve as strong signal generators for a later marketing concept. This shows that the economic efficiency and the existing equipment (electricity production, electricity consumption, storage) are the most important barriers to market introduction across regions and therefore critically reflect the overall result. However, various recommendations for action can be derived.